2011
DOI: 10.1167/iovs.10-6207
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Iron Chelator Deferiprone Protects against Iron Overload–Induced Retinal Degeneration

Abstract: Oral DFP was not toxic to the mouse retina. It diminished retinal iron levels and oxidative stress and protected DKO mice against iron overload-induced retinal degeneration. Further testing of DFP for retinal disease involving oxidative stress is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
82
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 53 publications
1
82
0
1
Order By: Relevance
“…Other researchers reported that DFP decreased retinal labile iron without retinal toxicity in the mouse. 19) These results suggest high ocular safety of DFP.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Other researchers reported that DFP decreased retinal labile iron without retinal toxicity in the mouse. 19) These results suggest high ocular safety of DFP.…”
mentioning
confidence: 81%
“…19) In the present study, we histologically and functionally examined whether intravitreal injection of DFP protects against tunicamycin-induced retinal degeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication has reported beneficial results of oral treatment with the iron chelator deferiprone in a mouse model where it ameliorated oxidative stress and prevented iron overload-induced retinal degeneration [147]. Moreover, several studies on other cultured cell lines have also shown supplementation with iron chelators to make cells less sensitive to H 2 O 2 exposure [148][149][150][151].…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…These authors previously demonstrated that this iron chelator can spare the retina from iron overload-induced degeneration, has no appreciable retinal toxicity in humans or mice, and is readily absorbed upon oral administration. 2 Deferiprone has been used for the management of thalassemia major 3 and is currently in clinical trials in the United States for treatment of contrast-induced acute kidney disease and for slowing the progression of chronic kidney disease (http://www.cormedix.com/pipeline_CRMD001.php). Drug repurposing is a current buzz phrase in translational medicine.…”
mentioning
confidence: 99%